20.7k views
4 votes
How do I do f(x)=-7x2/3-1g(x)=2x2/3+6 then find f(x)+g(x)

User Jithesh Kt
by
5.0k points

1 Answer

2 votes

ANSWER


f(x)+g(x)=-5x^(2/3)+5

Step-by-step explanation

To add two functions we have to add like terms. First let's write the functions in the sum:


f(x)+g(x)=(-7x^(2/3)-1)+(2x^(2/3)+6)

Like terms are those terms where the variable has the same exponent. In this operation we have two groups of like terms: two terms that cointain x^2/3 and two terms that contain x^0 (or in other words, where we can't see x):


f(x)+g(x)=(-7x^(2/3)+2x^(2/3))+(-1+6)

To add like terms we just have to add the coefficients:


\begin{gathered} f(x)+g(x)=(-7+2)x^(2/3)+5 \\ f(x)+g(x)=-5x^(2/3)+5 \end{gathered}

User Stensootla
by
5.2k points